Characterisation of the DNA sequence specificity, cellular toxicity and cross-linking properties of novel bispyridine-based dinuclear platinum complexes. Issue 1 (December 2016) - Johnson, Ben; Murray, Vincent; Temple, Mark
Abstract Background The anti-tumour activity of cisplatin is thought to be a result of its capacity to form DNA adducts which prevent cellular processes such as DNA replication and transcription. These DNA adducts can effectively induce cancer cell death, however, there are a range of clinical side effects and drug resistance issues associated with its use. In this study, the biological properties of three novel dinuclear platinum-based compounds (that contain alkane bridging linkers of eight, ten and twelve carbon atoms in length) were characterised to assess their potential as anticancer agents. Methods The properties of these compounds were determined using a DNA template containing seven tandem telomeric repeat sequences. A linear amplification reaction was used in combination with capillary electrophoresis to quantify the sequence specificity of DNA adducts formed by these compounds at base pair resolution. The DNA cross-linking ability of these compounds was assessed using denaturing agarose gel electrophoresis and cytotoxicity was determined in HeLa cells using a colorimetric cell viability assay. Results The dinuclear compounds were found to preferentially form DNA adducts at guanine bases and they exhibited different damage intensity profiles at the telomeric repeat sequences compared to that of cisplatin. The dinuclear compounds were found to exhibit a low level of cytotoxicity relative to cisplatin and their cytotoxicity increased as the linker length increased. Conversely, the interstrand cross-linking efficiency of the dinuclear compounds increased as the linker length decreased and the compound with the shortest alkane linker was six-fold more effective than cisplatin. Conclusions Since the bifunctional compounds exhibit variation in sequence specificity of adduct formation and a greater ability to cross-link DNA relative to cisplatin they warrant further investigation towards the goal of developing new cancer chemotherapeutic agents.